The use of palaeozoological methods in palaeoenvironment research of the Pomeranian Lakeland - Leszczyk, Aleksandra (Acta Geographica Lodziensia, 2024)
The paper summarises the results of palaeozoological analyses from sites in the Pomeranian Lakeland. The paper focuses on palaeozoological studies of biogenic sediments dating from the end of Odra Glaciation’s Warta Stadial to modern times. In the history of palaeoecological studies on the Pomerania Lakeland area, a significant role has been played by palaeobotanic analyses (mainly palynological) of the biogenic sediment. Palaeozoological analysis has included Cladocera, molluscs (Mollusca), testate amoebae (Testacea) and chironomids (Chironomidae). Sites were compared in terms of chronology of sediments, methods, resolution and location on different geological surface sediments. The paper draws attention to gaps in research into the palaeoenvironment of the Pomeranian Lakeland in the context of palaeozoological methods.